Si Blorok: Mother Figure as Performer of Islamic Education Values in Dongenge Pitik karo Bebek - Arum Rindu Sekar Kasih; Ummi Nurjamil Baiti Lapiana; Ika Oktaviana (Southeast Asian Journal of Islamic Education, 2023)
A fairy tale is a media parents use to instill good values ​​in children. In fairy tales, children can learn values embedded to strengthen their value education. One of the figures who often has a vital role in conveying values and becomes a role model is a mother figure. The mother figure in children’s stories or fairy tales can inspire parents in the family or teachers at school by providing an example of good behavior to the children. This study focused on Islamic education values in the character of Si Blorok, portrayed as a mother figure. This study used a qualitative descriptive approach by analyzing the character of Si Blorok. The data source was a fairy tale entitled "Dongenge Pitik karo Bebek" written by Impian Nopitasarihe data is the character of Si Blorok as a mother figure presenting Islamic education values through sentences or dialogues in the fairy tale. Another character in Dongenge Pitik karo Bebek became supporting data in analyzing the Islamic education values performed by Si Blorok. The data were analyzed by applying Menderop’s theories (2005), namely telling and showing methods to explore the character in the fairy tale. The results show that Si Blorok is regarded as a happy, loving and caring, loyal and patient, fair, active, and wise mother. Therefore, from an Islamic perspective, the figure mother, Si Blorok, has reflected as the first teacher to teach good values to children.